Enhancing Farmers’ Literacy on Foot-and-Mouth Disease through a Mobile Expert System Application in Labuhanbatu Utara: Peningkatan Literasi Peternak akan PMK (Penyakit Mulut dan Kuku) melalui Aplikasi Mobile Sistem Pakar di Labuhanbatu Utara - Hasibuan, Lailan Sahrina; Prayitno, Lilik; Giri, Endang Purnama; Kustiyo, Aziz; Adrianto, Hari Agung (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesia, causing distress among farmers due to their limited knowledge of how to handle the disease. This situation has been exploited by unscrupulous traders and middlemen who spread misinformation, claiming that cattle infected with FMD will inevitably die. Taking advantage of the panic, they purchase the animals at low prices and resell them at higher prices after treatment. To address this issue, a team of researchers from IPB University carried out a community outreach program aimed at improving farmers' literacy regarding FMD. As part of the program, a mobile-based expert system application was introduced, enabling farmers to perform quick, independent diagnoses based on observed symptoms. The evaluation results, based on pre-test and post-test assessments, showed a significant increase in farmers' understanding after attending the seminar. This innovation is expected to empower farmers to manage FMD more independently and effectively.